Okrnjeno delovanje endotelija - Janić, Miodrag (Medicinski razgledi, 2011)
Endothelial dysfunction represents one of the earliest changes in arterial function and is an important event in the atherosclerotic process. Reduced production or bioavailability of nitric oxide is the most important in the process of endothelial dysfunction, while on the other hand, it also includes a mismatch between the vasodilators and vasoconstrictors acting on the arterial wall. This article describes the role of normal endothelium and nitric oxide, as well as the pathophysiology of endothelial dysfunction. Clinically, endothelial function is assessed by noninvasive and invasive methods, listed in the article. The most commonly and widely used clinical method is noninvasive ultrasonographic flow mediated dilation measurement. Endothelial dysfunction is a reversible disorder that can be improved by nonpharmacological or pharmacological interventions. Healthy lifestyle is the principal non-pharmacological intervention. Currently the most promising of the pharmacological interventions are the pleiotropic effects of statins and inhibitors of the renin-angiotensin system.
Keywords: Endotelij žilni; Endothelium, Vascular; Physiopathology; Dušikov oksid; Nitric Oxide; Vazodilatacija; Dejavniki tveganja; Vasodilation; Risk Factors; Staranje; endotelij; Atherosclerosis; Diagnosis; žilni endotelij; Therapy; arterije; Aging; delovanje